A study protocol of a randomized controlled trial examining the efficacy of a symptom self‐management programme for people with acute myocardial infarction. (19th December 2014) - Klainin‐Yobas, Piyanee; Koh, Karen Wei Ling; Ambhore, Anand Adinath; Chai, Ping; Chan, Sally Wai‐Chi; He, Hong‐Gu
Abstract Aim To report a study protocol of a randomized controlled trial examining if a symptom self‐management programme helps patients with acute myocardial infarction self‐manage their physical and psychological symptoms. Background In addition to physical conditions, people with acute myocardial infarction often experience psychological symptoms. However, there is limited empirical evidence on how to help individuals self‐manage these psychological symptoms. Design A single‐blinded, randomized controlled trial is proposed. Methods A convenience sample of 90 will be recruited. Eligible participants will be adult patients with acute myocardial infarction hospitalized at a tertiary hospital in Singapore. Participants will be randomly assigned to one of the three treatment groups: Intervention 1 and standard care (n = 30), Intervention 2 and standard care (n = 30) and standard care alone (n = 30). Data will be collected by self‐reported questionnaires, physiological measures and open‐ended questions. Quantitative data will be analysed by descriptive statistics, t‐test, analysis of covariance and repeated measures analysis of variance. Open‐ended questions will be analysed by content analysis. Discussion This study will identify a potentially efficacious symptom self‐management programme for patients with acute myocardial infarction. If the efficacy of the programme is demonstrated, the programme can be integrated into hospital services to improve patient care. A new teaching method (virtual reality–based teaching) and new teaching materials (virtual reality videos and relaxation videos) derived from this study can be offered to patients. Future research with larger samples and multi‐centre recruitment can be undertaken to further test the efficacy of the interventions.